German trade performance in times of slumping euro area markets - Nils Jannsen; Stefan Kooths (Intereconomics, 2012)
While the global financial crisis had a strong impact on economic activity in Germany, the impact of the euro area crisis on economic activity in Germany has so far been relatively mild. Trade flows by region reveal that German firms have recently redirected their exports towards the remaining growth spots of the world economy, in particular to Asia's emerging economies. However, a continued crisis in the euro area is likely to put a considerable dent in German exports. While market forces have already triggered the rebalancing of intra-European trade flows, German exporters may play a helpful role in this process if firms in distressed countries circumvent high entry costs by integrating themselves into the global value chains of German exporters.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Wirtschaftskrise; Konjunktur; Eurozone; Außenhandelseffekt; Außenwirtschaft; Deutschland